1992
DOI: 10.1200/jco.1992.10.6.969
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sucralfate on acute and late bowel discomfort following radiotherapy of pelvic cancer.

Abstract: It is suggested that sucralfate can be of beneficial value in diminishing bowel discomfort during treatment and, most importantly, sucralfate also reduces the late bowel disturbances that follow radiotherapeutic treatment of pelvic malignancies. The earlier proposed mechanisms of action (eg, protection of denuded mucosa, cytoprotective properties, binding bile acids) seem adequate to explain the present effects of sucralfate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(49 citation statements)
references
References 19 publications
1
46
0
2
Order By: Relevance
“…Sucralfate also reduces intestinal discomforts in patients treated with pelvic fields (20,21,25). Data are comparable since the only change in treatment technique was the conversion to conformal radiotherapy technique, including the prostate, with a 2-cm margin.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Sucralfate also reduces intestinal discomforts in patients treated with pelvic fields (20,21,25). Data are comparable since the only change in treatment technique was the conversion to conformal radiotherapy technique, including the prostate, with a 2-cm margin.…”
Section: Discussionmentioning
confidence: 99%
“…One group of patients was treated with conventional 4-field box technique including the pelvic region. Those patients were also included in a double-blind, prospective, randomized study comparing placebo and sucralfate during treatment (21). Seventy patients were included in that study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Topical treatments such as antiinflammatory enemas and suppositories are usually considered first-line therapy, but studies evaluating their protective role have shown mixed results. Two double-blind, placebocontrolled trials have shown improved stool consistency and reduced frequency in patients using sucralfate enemas, 34,35 as well as a reduction in severity of rectal bleeding after 4 weeks of treatment. 36 Others have suggested that sucralfate enemas do not reduce the rate of rectal bleeding and may even be associated with worsened bowel function.…”
Section: Nonsurgical Therapymentioning
confidence: 99%